The Impact Of The Special Dividend Announcement On The Stock Return: The Case Of Malaysia. - Dehghani, Pegah; Loo , Sin Chun (Jordan Whitney, 2011)
The method of distributing excess cash among investors is determined by dividend policies taken by each company. Usually, there are three alternatives of the excess cash distribution; offering special dividend, initiating or increasing regular dividend and repurchase share. Special dividend that is a one-time payment rather than the permanent increase in cash payment conveys the good news that although the current financial situation of the firm might not be sustainable, but distribution of the special dividend reduces the free cash flow problems. Furthermore, distribution excess cash via a special dividend would suggest that managers believe that the current share price of company is not undervalued. This study investigates the impact of the special dividend announcement on the stock returns of the Malaysian stock market. Using the standard event study methodology, the findings indicate that, the special dividend announcement signals good news to investors in the overall market and when the analysis expanded to the sector level. That causes the stock returns to react positively and immediately when the news is announced. These findings are in line with the findings of previous studies carried out in US and Australia. [ABSTRACT FROM AUTHOR]